Urban Safety Nets – Experiences from Three Countries : Benin, Republic of Congo, and Mali - Moreira, Vanessa; Gentilini, Ugo (World Bank, Washington, DC, 2016)
As countries implement social safety nets programs, a range of technical hurdles affects their implementation differently in rural and urban areas. In urban areas, the focus of this study, living in is expensive and more vulnerable at economy slowdowns. Poverty can be more severe than in rural areas and accompanied by high malnutrition rates. Challenges faced by poor populations in most urban areas related to the lack of proper identification,outreach, intake and registration of potential beneficiaries in part due to the lack of social cohesion and the existence of multiple channels of communication, challenging the delivery of any messages quickly and efficiently. Therefore social workers have a fundamental part during program implementation and Monitoring and evaluation (M&E) process.